Comparison of cerebral oxygen desaturation events between children under general anesthesia and chloral hydrate sedation - a randomized controlled trial - Philipp Gude; Thomas P. Weber; Stefan Dazert; Norbert Teig; Philipp Mathmann; Adrian I. Georgevici; Katrin Neumann (BMC, 2022)
Abstract Background During pediatric general anesthesia (GA) and sedation, clinicians aim to maintain physiological parameters within normal ranges. Accordingly, regional cerebral oxygen saturation (rScO2) should not drop below preintervention baselines. Our study compared rScO2 desaturation events in children undergoing GA or chloral hydrate sedation (CHS). Methods Ninety-two children undergoing long auditory assessments were randomly assigned to two study arms: CHS (n = 40) and GA (n = 52). Data of 81 children (mean age 13.8 months, range 1-36 months) were analyzed. In the GA group, we followed a predefined 10 N concept (no fear, no pain, normovolemia, normotension, normocardia, normoxemia, normocapnia, normonatremia, normoglycemia, and normothermia). In this group, ENT surgeons performed minor interventions in 29 patients based on intraprocedural microscopic ear examinations. In the CHS group, recommendations for monitoring and treatment of children undergoing moderate sedation were met. Furthermore, children received a double-barreled nasal oxygen cannula to measure end-tidal carbon dioxide (etCO2) and allow oxygen administration. Chloral hydrate was administered in the parent's presence. Children had no intravenous access which is an advantage of sedation techniques. In both groups, recommendations for fasting were followed and an experienced anesthesiologist was present during the entire procedure. Adverse event (AE) was a decline in cerebral oxygenation to below 50% or below 20% from the baseline for ≥1 min. The primary endpoint was the number of children with AE across the study arms. Secondary variables were: fraction of inspired oxygen (FIO2), oxygen saturation (SpO2), etCO2, systolic and mean blood pressure (BP), and heart rate (HR); these variables were analyzed for their association with drop in rScO2 to below baseline (%drop_rScO2). Results The incidence of AE across groups was not different. The analysis of secondary endpoints showed evidence that %drop_rScO2 is more dependent on HR and FIO2 than on BP and etCO2. Conclusions This study highlights the strong association between HR and rScO2 in children aged < 3 years, whereas previous studies had primarily discussed the role of BP and etCO2. Prompt HR correction may result in shorter periods of cerebral desaturation. Trial registration The study was retrospectively registered with the German Clinical Trials Registry (DRKS00024362, 04/02/2021).